Optimal control and viscosity solutions of Hamilton-Jacobi-Bellman equations - Bardi, Martino; Capuzzo-Dolcetta, Italo (Modern Birkhäuser Classics, 1997)
This softcover book is a self-contained account of the theory of viscosity solutions for first-order partial differential equations of Hamilton-Jacobi type and its interplay with Bellman's dynamic programming approach to optimal control and differential games.